The impact of a Post-Take Ward Round Pharmacist on the Risk Score and Enactment of Medication-Related Recommendations - Brooke Bullock; Peter J Donovan; Charles Mitchell; Jennifer A Whitty; Ian Coombes (MDPI AG, 2020)
There is a scarcity of published research describing the impact of a pharmacist on the post-take ward round (PTWR) in addition to ward-based pharmacy services. The aim of this paper was to evaluate the impact of clinical pharmacists’ participation on the PTWR on the risk assessment scores of medication-related recommendations with and without a pharmacist. This includes medication-related recommendations occurring on the PTWR and those recommendations made by the ward-based pharmacist on the inpatient ward. A pre−post intervention study was undertaken that compared the impact of adding a pharmacist to the PTWR compared with ward-based pharmacist services alone. A panel reviewed the risk of not acting on medication recommendations that was made on the PTWR and those recorded by the ward-based pharmacist. The relationship between the risk scores and the number and proportion of recommendations that led to action were compared between study groups. There were more medication-related recommendations on the PTWR in the intervention group when a pharmacist was present. Proportionately fewer were in the ’very high and extreme’ risk category. Although there was no difference in the number of ward pharmacist recommendations between groups, there was a significantly higher proportion of ward pharmacist recommendations in the “very high and extreme” category in those patients who had been seen on a PTWR attended by a pharmacist than when a pharmacist was not present. There were a greater proportion of “low and medium” risk actionable medication recommendations actioned on the PTWR in the intervention group; and no difference in the risk scores in ward pharmacist recommendations actioned between groups. Overall, the proportion of recommendations that were actioned was higher for those made on the PTWR compared with the ward. The addition of a pharmacist to the PTWR resulted in an increase in low, medium, and high risk recommendations on the PTWR, more very high and extreme risk recommendations made by the ward-based pharmacist, plus an increased number of recommendations being actioned during the patients’ admission.